Robust perturbed linear-quadratic control problem on semi-infinite interval with applications - Manowong R. (2014)
In this paper, we describe a complete solution of the linear-quadratic control problem on a semi-infinite interval with the linear term in the objective function and polytropic uncertainty on a linear system. An application on an innate immune response is considered.